2005
DOI: 10.1080/02687030444000732
|View full text |Cite
|
Sign up to set email alerts
|

Development and reliability of a quantitative measure of adults' narratives

Abstract: Background: Assessing narrative discourse production in persons with aphasia has long challenged clinicians seeking to improve functional outcomes. Fortunately, the development of single picture or picture sequence stimuli has enabled clinicians to quantify aspects of elicited narrative discourse production in a clinical context. However, also needed for the analysis of the narrative discourse of individuals with aphasia are performance data for adults without brain damage. Such comparative data of both younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 9 publications
9
44
0
4
Order By: Relevance
“…We found that narrative, variety, and discourse comprehension were affected by ageing and low education. These parameters considered richness and variety of conceptual ideas and cohesion between utterances that might easily be similar to those investigated by Doung and Ska (2001) and Harris Wright et al (2005). These findings are also in line with previous investigations that showed changes in the macrolinguistic aspects of discourse production such as quantity, precision, cohesion, and organisation of the language production occurring with increasing age (Critchley, 1984;Obler, 1989; see for a review Brownell & Joanette, 1993).…”
Section: Analysis Of Conversational Abilitiessupporting
confidence: 80%
See 2 more Smart Citations
“…We found that narrative, variety, and discourse comprehension were affected by ageing and low education. These parameters considered richness and variety of conceptual ideas and cohesion between utterances that might easily be similar to those investigated by Doung and Ska (2001) and Harris Wright et al (2005). These findings are also in line with previous investigations that showed changes in the macrolinguistic aspects of discourse production such as quantity, precision, cohesion, and organisation of the language production occurring with increasing age (Critchley, 1984;Obler, 1989; see for a review Brownell & Joanette, 1993).…”
Section: Analysis Of Conversational Abilitiessupporting
confidence: 80%
“…Low education affected performance only in the older group. Similar results were reported also by Harris Wright et al (2005) who showed that older subjects produced less information on main events in a narrative production task based on pictures or picture sequences.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Wright and colleagues (Wright, Capilouto, Wagovich, Cranfill, & Davis, 2005) developed a main events measure for use with the Nicholas and Brookshire (1993) picture stimuli (two single and two sequential picture stimuli). A main event was operationally defined as an event of sufficient importance to the story as a whole and independent from the other events in the story , 2006Wright et al, 2005). Resulting main events represented the sequential and/or temporal story schema depicted in the picture(s).…”
mentioning
confidence: 99%
“…Muitos estudos têm utilizado a sequência de figuras para eliciar a narrativa em indivíduos sem comprometimento cognitivo e os resultados demonstram que adultos jovens apresentam desempenho melhor nas medidas de informatividade e conteúdo durante a produção do discurso, quando comparados com adultos mais velhos (Duong, Ska, 2001;Capilouto et al, 2005;Wright et al, 2005).…”
Section: Envelhecimento E Discursounclassified